The working dread? Analysing the impact of the Hukou reform on firms' monopsony power in China - Brzezinska, I (Centre for the Study of African Economies, 2021)
This paper uses firm-level data from the Chinese Annual Survey of Industrial Firms (CASIF) for the years 1998-2007 to analyse the impact of the household registration system (Hukou) reform in China on monopsony power of firms. I adopt a multiple-period difference-in¬differences framework to exploit the non-uniform labour market reform implementation. By comparing firms in cities that adopted the reform to firms in cities that did not, I find that relaxing restrictions on geographical labour mobility decreased firms’ monopsony power overall. Further heterogeneity analysis suggests that the effect can be decomposed into two offsetting forces: firms in big cities saw their monopsony power increase, while it diminished for firms in small cities. Consistent with a decrease in monopsony power, firms in reform cities spent 26% more on the worker housing fund and 7% more on unemployment insurance as a result of the Hukou reform. I find that the Hukou reform is positively related with both marginal and average products of labour.